Alloying for orbital alignment enables thermoelectric enhancement of EuCd2Sb2. Issue 20 (9th May 2019) - Zheng, Liangtao; Li, Wen; Wang, Xiao; Pei, Yanzhong
Abstract : Alloying EuCd2 Sb2 with EuZn2 Sb2 enables a valence band alignment and a reduction in lattice thermal conductivity resulting in a substantial thermoelectric improvement. Abstract : Alignment of doubly degenerate p xy and nondegenerate p z band orbitals at the Γ point in the Brillouin zone for high orbital degeneracy has been demonstrated as an effective strategy for advancing thermoelectric AB2 C2 Zintl compounds in p-type conduction. Formation of solid solutions of different compounds with opposite energy offsets between p xy and p z orbitals would enable a minimization of energy offset to realize an orbital alignment, and thereby lead to an enhanced electronic performance. Here we show that alloying EuCd2 Sb2 with EuZn2 Sb2 not only effectively aligns the p xy and p z valence bands for superior electronic performance, but also significantly reduces the lattice thermal conductivity resulting from the phonon scattering by alloy defects. Eventually, the average thermoelectric figure of merit ( zT ) of the EuCd1.4 Zn0.6 Sb2 alloy is enhanced by at least 35% compared to that of pristine EuCd2 Sb2 and the alloying agent EuZn2 Sb2, demonstrating that this alloy is a promising thermoelectric material.